Comparison of Pain Scale and Duration of Early Mobilization after Cesarean Section Surgery Using Eracs Tap Block Method with Eracs without Tap Block - Siburian, Tissa Priscillya Deabitha Br; Simbolon, Boyke Marthin; Chairul, Muhammad (Journal La Medihealtico, 2024)
One of the problems for pregnant women is dealing with pain and recovering quickly after surgery. This research focuses on observing pregnant women after surgery to compare the pain scale and duration of early post-operative mobilization using ERACS tap blocks and ERACS without tap blocks. This quantitative research was designed using a cross-sectional approach. The research sample was 40 respondents selected by purposive sampling. The pain scale was measured using the Visual Analog Scale (VAS) and Early Mobilization was measured using an observation sheet. Based on the results of statistical analysis. The p value in the results of the Mann-Whitney test analysis on the pain scale for both variables is VAS5 (24 hours) which has a p value of 0.028 which is lower than 0.05. Early mobilization shows that catheter removal has a p value of 0.002, lower than 0.05. It can be concluded that there is a significant difference between the pain scale and the duration of early mobilization using ERACS tap block and ERACS without tap block.